Perencanaan Kapasitas Produksi Paving Guna Memenuhi Permintaan Pada Cv. Rejeki Beton Perkasa - In'am Maulana Fayrus Abadi; Siti Mundari (Lembaga Pengembangan Kinerja Dosen, 2023)
CV. Rejeki Beton Perkasa is a company that produces paving. CV. Perkasa Beton Fortune has problems in fulfilling consumer requests. Given the large customer orders, the company must improve the production schedule to meet the company's production capacity, because it can be seen that the company still does not have long-term planning and production capacity that is mature, which results in uncontrolled production processes and delays in meeting consumer demand. The effort undertaken is planning production capacity requirements using the Rough Cut Capacity Planning (RCCP) approach to fulfill customer orders. The results of the completion of Rough Cut Capacity Planning (RCCP) showed that the work center for making raw materials, mixing, printing and sprinkling experienced a capacity shortage in the period 21,22,23,24 while for the mixing and screening work center experienced a capacity shortage in the period 22,23, 24. The raw material manufacturing work center experienced a capacity shortage of 366 hours, the mixing work center 214 hours, the sifting work center 6 hours, the mixing work center 15 hours, the printing work center 291 hours, the watering work center 180 hours. The proposed production capacity planning obtained from the researchers is to add overtime hours for work centers that experience capacity shortages with a total cost of Rp. 21.500,000.